William of Corbeil and the Canterbury York Dispute - Bethell, Denis (The journal of ecclesiastical history, 1968)
The immediate purpose of this article is narrative, in particular its aim is to draw attention to two little-known incidents in the early life of William of Corbeil, archbishop of Canterbury (1123–36) and to a rearrangement of the chronology of the Canterbury-York dispute in the 1120s, and, in general, to tell part of the story of that dispute again. The story is worth telling because it is colourful and dramatic and crowded with incident, because it is almost all that we know of a remote and thinly-documented period of English Church history, and because it marks an entirely new interest in English affairs on the part of the popes, who took part in the dispute with an energy and effect unparallelled since the seventh century. Despite (or perhaps because of) the excellence of the sources—Eadmer, monk of Canterbury, and Hugh, precentor of York—the story has only once been told at all fully for its most important period, that from 14 August 1114 to 9 December 1128—by Mr. Nicholl, in his recently published ‘Life’ of Thurstan, archbishop of York (1114–40). Naturally, he concentrated on Thurstan, the greater man of the two, the man with the better case, the victor in the dispute, of whom much more is known. This article is intended to give a brief synopsis of the early life of the loser, to tell of his early introduction to the dispute and his eventual part in it.